2009
DOI: 10.1890/07-1751.1
|View full text |Cite
|
Sign up to set email alerts
|

Delayed conifer mortality after fuel reduction treatments: interactive effects of fuel, fire intensity, and bark beetles

Abstract: Abstract. Many low-elevation dry forests of the western United States contain more small trees and fewer large trees, more down woody debris, and less diverse and vigorous understory plant communities compared to conditions under historical fire regimes. These altered structural conditions may contribute to increased probability of unnaturally severe wildfires, susceptibility to uncharacteristic insect outbreaks, and drought-related mortality. Broad-scale fuel reduction and restoration treatments are proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 67 publications
1
31
0
Order By: Relevance
“…Thirty-three percent of sites were treated with either pile or broadcast burning after harvesting in order to address natural and activity fuels. Burning reduces surface fuels but also produces direct and indirect tree mortality [44][45][46]; over time, fire-killed snags enter the surface fuel pool. Indeed, in burned sites, the number of snags in the most recently treated stands was 1.4-6.7 times that of the next age class, indicating that some trees killed during burning and still standing 2-4 years after treatment will become part of the surface fuel pool in the coming years.…”
Section: Ground and Surface Fuelsmentioning
confidence: 99%
“…Thirty-three percent of sites were treated with either pile or broadcast burning after harvesting in order to address natural and activity fuels. Burning reduces surface fuels but also produces direct and indirect tree mortality [44][45][46]; over time, fire-killed snags enter the surface fuel pool. Indeed, in burned sites, the number of snags in the most recently treated stands was 1.4-6.7 times that of the next age class, indicating that some trees killed during burning and still standing 2-4 years after treatment will become part of the surface fuel pool in the coming years.…”
Section: Ground and Surface Fuelsmentioning
confidence: 99%
“…Laughlin and Abella [21] and Laughlin et al [22] applied SEM to an observational study of abiotic and biotic factors influencing plant community composition and species richness in a ponderosa pine (Pinus ponderosa P. and C. Lawson) forest ecosystem. Youngblood et al [23] studied the effects of experimental thinning and prescribed burning treatments on mortality of ponderosa pine with ANOVA and SEM. They found that SEM was able to represent and detect cascading effects of several firerelated factors on mortality, a process that the ANOVA model could not represent.…”
Section: Introductionmentioning
confidence: 99%
“…Models of such interactions mainly focused on descriptive, statistical approaches, including various logistic regression models (Bebi et al, 2003;Bigler et al, 2005;Breece et al, 2008), generalized linear models with different link functions (Peltonen, 1999;Eriksson et al, 2005;Hood and Bentz, 2007) and classification tree models (Kulakowski and Veblen, 2007). As an alternative approach for evaluating hypotheses and conceptual understanding about fire-bark beetle interactions, Youngblood et al (2009) demonstrated the utility of structural equation modelling. In a more process-oriented approach Seidl et al (2007) used a dynamically calculated estimate of drought-induced host tree stress to account for increasing tree susceptibility to I. typographus attack.…”
Section: Interactions With Other Disturbance Agentsmentioning
confidence: 99%
“…In this regard statistical modelling can provide insights on quantitative relationships for exploratory research questions. For example, structural equation modelling (e.g., Youngblood et al, 2009) or hierarchical Bayesian methods (e.g., McMahon et al, 2009) are particularly suitable for such tasks, allowing the consideration of simultaneous (and interacting) drivers as well as of non-Gaussian, nested and random effects. Furthermore, recent methodological advances have improved our inference abilities in working with the highly variable, incomplete and noisy characteristics of most disturbance datasets (e.g., machine learning algorithms such as random forests, genetic algorithms, and neural networks).…”
Section: Challenges For Disturbances Modelling Under Climate Changementioning
confidence: 99%